Our deep gossip : conversations with gay writers on poetry and desire - Hennessy, Christopher, 1973- (The University of Wisconsin Press, 2013)
The author interviews eight gay men who are celebrated American poets and writers: Edward Field, John Ashbery, Richard Howard, Aaron Shurin, Dennis Cooper, Cyrus Cassells, Wayne Koestenbaum, and Kazim Ali. The interviews showcase the complex ways art and life intertwine, as the poets speak about their early lives, the friends and communities that shaped their work, the histories of gay writers before them, how sex and desire connect with artistic production, what coming out means to a writer, and more.